Beyond connection: Social media, isolation, and sociability among Saudi university students - Altigani, Abdelrahman; Almubarak, Abdullah Jafar; Moidi, Ibrahim Fahad; Alqahtani, Yousef Saeed; Altalalwah, Mohammad Abdulljalil; Alqarni, Mohammed Salem; Algosaibi, Hamad Abdullah (Edelweiss Applied Science and Technology, 2026)
This study investigates whether social media use enhances or weakens sociability among Saudi university students. Using a web-based cross-sectional design, data were collected from 250 students enrolled in the College of Computer Science and Information Technology at Imam Abdulrahman bin Faisal University. The findings reveal a mixed relationship between social media use and social behavior. Moderate use appears to support communication, connectedness, and self-expression, while heavier use is associated with reduced face-to-face interaction, loneliness, and exposure to harmful online experiences such as cyberbullying. The results suggest that social media does not exert a uniformly positive or negative influence on sociability; rather, its effects depend on the intensity and purpose of use and on whether online interaction complements or displaces offline relationships. This study provides context-specific evidence from Saudi Arabia and contributes to the broader discussion on the social consequences of digital communication among university students. The findings also have practical implications for educators and policymakers by highlighting the need to encourage balanced, responsible, and intentional social media use to support students’ social well-being.